Housing Complaints, Institutional Anomalies, and Red Tape: New Aspects of an Old Debate - Litvintsev, Denis (Journal of Economic Sociology, 2024)
The article develops a discussion about the dysfunctionality of the institution of complaints in the housing and communal services sector in Russia, which began in 2022–2023 with a series of articles by D. B. Litvintsev and O. E. Bessonova, published in the “Journal of Economic Sociology.” This work is mainly based on a discussion of the speech of A. D. Abdulaev with a thematic report at a seminar of the Higher School of Economics in March 2024. The article touches on such issues as the need to expand a strictly institutional approach to an integrative one, the limitations of quantitative methods in the study of the institution of complaints, the problem of institutional anomalies in the functioning of the institution of complaints, and also discusses the phenomenon of red tape. Particular attention is paid to the problem of analyzing electronic complaints filed through various Internet portals and the inability to fully get rid of institutional abuses through formalization and moderation of complaints filed. As a new aspect of the discussion, it is proposed to consider housing complaints as a special type of complaint (by analogy with housing activism as a special type of social activism). To do this, the author of this article turns to the extensive experience of the UK, which has a centralized channel for filing housing complaints—the Housing Ombudsman Service, which operates in accordance with the Complaint Handling Code and conducts annual public reporting on its activities, publishing results and ratings in the public domain on its official website. In conclusion, the need to develop a positive culture of complaints in the housing and communal services sector in Russia is noted, which requires further research and the development of appropriate recommendations.